Mastering the Language of Service: English Communication Skills for Food and Beverage Professionals - Asriyani, Retny; Anggayana, I Wayan Agus (Akademi Komunitas MAPINDO, 2023)
This article aims into the crucial role of English language skills in the industry, emphasizing the need forprofessionals to master communication for enhanced customer experiences and career advancement. Englishcommunication skills are vital for career advancement. As professionals in the food and beverage industry aimto move up the ladder, whether it be from waiter or from line cook to sous chef, the ability to effectivelycommunicate becomes increasingly important. Strong English skills allow professionals to confidently interactwith senior management, participate in important meetings, and articulate their ideas and concerns. This notonly enhances their chances for promotion but also positions them as valuable assets to their employers. Thisresearch is descriptive qualitative research. 15 Competence units, 46 elements of competence were found inthis research.Keywords: Language of Service, English Communication, Skills, Food and Beverage, Professionals